IDENTIFICATION OF CAREER MANAGEMENT SKILLS RELATED PROBLEMS IN THE STUDY PROCESS OF PODOLOGISTS - Saulīte, Mārīte; Andersone, Rudīte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Despite the competencies acquired in study process, results of learning, diploma and provided guidance measures podologs as same as other young specialists often lack skills to create successful proffesional career in their field.At this moment in Latvia, specific proffesion, including podologs, career management skill set is not defined. For students of podology learning of mentioned skills is indirectly integrated in educational process, which is reflected by the study program aims, methods and expected results.The aim of the article is to analyse career management skills identification problems in study process of podologs and in this regard, by empirical research results on podologs career management skills in the study process.